SDSS J122958.84+000138.0: a compact, optically red galaxy - Paudel, Sanjaya; Lisker, Thorsten; Huxor, Avon P. (Arxiv, 2016)
We report a new compact galaxy, SDSS J122958.84+000138.0 (SDSS J1229+0001), which has unique morphological and stellar population properties that are rare in observations of the nearby universe. SDSS J1229+0001 has an $r$-band absolute magnitude (M$_{r}$) and half-light radius (R$_{h}$) of $-$17.75 mag and 520 pc, respectively. Located in a fairly low density environment, morphologically it is akin to a typical early-type galaxy as it has a smooth appearance and red colour. But, interestingly, it possesses centrally concentrated star forming activity with a significant amount of dust. We present an analysis of structural and stellar population properties using archival images and VLT/FORS2 spectroscopy. Analysis of UKIDSS H-band image shows that the observed light distribution is better fitted with two components S\'ersic function with inner and outer component effective radii 190 and 330 pc, respectively. Whereas, overall half-light radius measured in H-band is much smaller compared to optical, i.e 290 pc. We prepared a Spectral Energy Distribution (SED) from optical to FIR and interpret it to derive star-formation rate, dust mass and stellar mass. We find that the SDSS J1229+0001 has dust mass M$_{dust}$ = 5.1 $×$ 10$^{5}$ M$_{\sun}$ with a dust to stellar mass ratio log(M$_{dust}$/M$_{*}$) = $-$3.5. While the observed stellar population properties are -- to some extent -- similar to that of a typical S0 galaxy, a unified view from stellar population and structural properties may suggests that SDSS J1229+0001 is a {\it smoking gun} example of a compact early-type galaxy in formation.